TECHNOLOGY FOR CREATING AN ELECTRONIC TUTORIAL (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article provides information about the software tools of training, including the creation of electronic tutorials, their software interface and its capabilities, the tasks of existing devices in the software interface and their analysis, software tools used in the creation of an electronic tutorial and their capabilities. In particular, the instruction for creating and using an electronic training manual is given as an example of the subject "Object-oriented programming".